2011
DOI: 10.9753/icce.v32.sediment.55
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Model of 3d Morphodynamic After Offshore Nourishment

Abstract: A three-dimensional model of morphodynamics after offshore nourishment was developed. In the presented model, the 3D beach evolution model that is not only after nourishment but also taking into account the nourishment process of injected sand material. In order to consider the injected process of sand, the computation using the advectiondiffusion equation for suspended sediment concentration was adapted in the model. The presented model was applied to an idealized beach with two groins in order to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In the model, the coastal area model using Q-3D nearshore current model, proposed by Kuroiwa et al(2010) was modified so as to be considered the influence of sea bottom with non-eroded hard bottom such as shore reef.…”
Section: Numerical Modelmentioning
confidence: 99%
“…In the model, the coastal area model using Q-3D nearshore current model, proposed by Kuroiwa et al(2010) was modified so as to be considered the influence of sea bottom with non-eroded hard bottom such as shore reef.…”
Section: Numerical Modelmentioning
confidence: 99%
“…In this study, Multi-directional random wave model based on the wave action balance equation proposed by Mase et al(2004) was newly added the previous 3D model presented by Kuroiwa et al(2010). The presented model in this study consists of four modules as shown in Fig.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Many three-dimensional beach evolution models have been proposed and then applied to practical evaluation of the construction of coastal structures, the accretion problems of the navigation channel of ports and so on. We have develop a coastal area model with shoreline change based on the quasi-three dimensional (Q-3D) nearshore current model (Kuroiwa et al, 2004), and applied to 3D morphodynamics around river-mouth (Kuroiwa et al,2008) and after shoreface nourishments (Kuroiwa et al,2010). However, the hydrodynamic module in the previous models, which is based on the wave energy balance equation and the Q-3D nearshore current model, was not considering the wave-current interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed coastal area model was based on the hybrid model proposed by Kuroiwa et al (2006Kuroiwa et al ( ,2010. The coastal area model presented in this study consists of three modules; 1) a wave module, 2) a nearshore current module, 3) a sediment transport and a water depth change evolution module, as shown in Fig.1.…”
Section: Numerical Modelmentioning
confidence: 99%